2016
DOI: 10.2106/jbjs.15.00280
|View full text |Cite
|
Sign up to set email alerts
|

Age and Preoperative Knee Society Score Are Significant Predictors of Outcomes Among Asians Following Total Knee Arthroplasty

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 35 publications
7
72
0
Order By: Relevance
“…No significant differences were seen between responders and non‐responders in the majority of demographic and clinical factors considered, including sex, BMI, diabetes, joint replaced, type of prosthesis used, and surgeons. Our results were consistent with previous reports . However, previous studies have also found higher age, sex, higher BMI, comorbidities, and joint replacement to be predictors of non‐responders using various PROMs, including the Oxford Knee Score, Short Form 36, EQ‐5D health questionnaire, and WOMAC .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No significant differences were seen between responders and non‐responders in the majority of demographic and clinical factors considered, including sex, BMI, diabetes, joint replaced, type of prosthesis used, and surgeons. Our results were consistent with previous reports . However, previous studies have also found higher age, sex, higher BMI, comorbidities, and joint replacement to be predictors of non‐responders using various PROMs, including the Oxford Knee Score, Short Form 36, EQ‐5D health questionnaire, and WOMAC .…”
Section: Discussionsupporting
confidence: 93%
“…However, the predictive power of these associations varies between studies; while Judge et al reported female sex was a predictor of function non‐response to THR, Weber et al reported male sex was a predictor of pain and function non‐response to both TKR and THR . Similar inconsistencies are seen with other commonly reported variables including age, BMI, comorbidities, pre‐operative pain scores, and pre‐operative function scores . The lack of consistency could be attributed to a number of factors within these studies, including variation in the definition of the MCID, type of joint replacement, and distinction between pain and function in outcome.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Although worse pre‐operative pain and patient‐reported function and quality of life have been associated with lower post‐operative absolute scores, it should be noted that often the improvement (difference between post‐operative and pre‐operative scores) is greater in patients with lower pre‐operative scores . This makes intuitive sense but may be due to ceiling effects in some scores used, whereby patients with less severe pre‐operative symptoms have less room to improve.…”
Section: Patient Characteristics Influencing Decision Makingmentioning
confidence: 99%
“…Age is another factor that is actively related to the period after surgery, 28 being an important predictor of functional outcome. 30 In the study, patients older than 70 years presented a relative frequency of 45.45% in the intervention group and 43.47% in the control group.…”
Section: Eficácia Do Tratamento Adjuvante Da Dor Pós-artroplastia Totmentioning
confidence: 76%